The Three Ni Doctrine of Healing the World: A New Breakthrough in Qing Dynasty Daoism’s Interpretation of the “Inner Sage, Outer King” Ideal Within the Three Teachings Unity Movement - Yuhao Wu (Religions, 2025)
The Three Ni Doctrine of Healing the World 三尼醫世說 is a product of the Three Teachings Unity 三教合一 movement during the Ming and Qing dynasties. This doctrine is believed to have been directly transmitted by Confucius (Ch. Zhong Ni 仲尼), Shakyamuni (Ch. Mu Ni 牟尼), and Laozi (Ch. Qing Ni 青尼), which is why it is referred to as the “Three Ni”. After being extensively refined by the Qing dynasty Daoist Min Yide, the doctrine evolved into a complete theoretical system for healing the world. It advocates for the connection between humans and the world through “qi” 氣. By properly regulating the qi within the individual, one can influence the qi of the world, thereby achieving governance of the world through personal inner alchemical cultivation. The doctrine addresses the challenge of reconciling personal cultivation with the salvation of all beings after Daoism’s decline in political influence. It marks a significant breakthrough in the traditional Chinese ideal of “Inner Sage, Outer King” 內聖外王. Furthermore, Min integrated the Three Ni Doctrine with the Celestial Immortality teachings of Jing’ai Mountain Daoism, creating a systematic Daoist orthodoxy known as the “Heart Lineage of the Most High” (Ch. Taishang Xinzong 太上心宗). This initiative highlights the courage of Qing dynasty Daoist elites in reforming themselves to preserve Daoism’s status within the broader context of the Three Teachings Unity movement.